1932
DOI: 10.1002/zaac.19322070102
|View full text |Cite
|
Sign up to set email alerts
|

Schmelzdiagramme höchstfeuerfester Oxyde. IV. (Aluminiumoxyd)

Abstract: 1. Die Schmelzpunkte von Cr2O3 2275°, La2O3 2315°, Ga2O3 1740° sind neu bestimmt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

1934
1934
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…According to the results of this investigation, the AI20 3-Th02 eutectic is at 1,910 0 C and 60.7 wt percent of A120 3 or, in mole ratio, at 4A120 3 :Th02, which is in good agreement with the findings of Wartenburg and Reusch [15]. The location of the eutectic ( fig.…”
Section: The System Beo-ahoa-th02supporting
confidence: 91%
See 1 more Smart Citation
“…According to the results of this investigation, the AI20 3-Th02 eutectic is at 1,910 0 C and 60.7 wt percent of A120 3 or, in mole ratio, at 4A120 3 :Th02, which is in good agreement with the findings of Wartenburg and Reusch [15]. The location of the eutectic ( fig.…”
Section: The System Beo-ahoa-th02supporting
confidence: 91%
“…As a generalization, one can say that the beginning of fusion of the ternary mixtures will average about 50 deg C lower than for corresponding mixtures in the BeO-Al20 3-Th02 system, but the binary eutectics of the end members are about the same in the two systems. The eutectic between Al20 3 and zr02 at about 50 mole percent, or 55 wt percent, of zr02 has been reported at 1,920 0 C [25] and at 1,900° C [15]. In this study, fusion was observed at 1,885° C. For thesystem BeO-Zr02, a compound (3BeO:2Zr02) and two eutectics were reported in 1930 [26] , but a year later a single eutectic at about 75 wt percent of zr02 and 2,240° C was reported [27].…”
Section: The System Beo-alo·zr02mentioning
confidence: 96%
“…When h eated at 1,950 0 C, a very fluid melt was formed. These data support the finding of Wartenburg and Reusch [16] of a eutectic melting at about 1,900 0 C.…”
Section: Materials and Experi Mental Mixt Uressupporting
confidence: 91%
“…Beryllia and alumina.-The information published by Wartenburg [16] shows a fairly sharp eutectic at 1,890° ° for a mixture of BeO and Al20 3 in the 1:1 mole ratio. He points out that there was no evidence of the formation of chrysoberyl.…”
Section: Thoria and Magnesia-an Intimate Mixture In The Mole Ratio 40mentioning
confidence: 99%
“…Figure 2 shows the calculated optimized phase diagram of the Al 2 O 3 -TiO 2 system in air. The diagram was first studied by von Wartenberg and Reusch 14) and by Bunting.…”
Section: Critical Evaluation and Optimization Of Thementioning
confidence: 99%